(untitled) (BISTUA Revista de la Facultad de Ciencias Básicas, 2024)
Since the production of conventional oil and gas is declining while costs are increasing, in recent years focus of interest directed toward unconventional reservoirs. The integral evaluation of unconventional reservoirs is based on multi-scale imaging and analysis, which includes X-ray Computed Tomography, X-ray Micro-Computed Tomography, Quantitative Evaluation of Minerals by Scanning Electron Microscopy and Focused Ion Beam Scanning Electron Microscopy, which can be integrated each other to provide a dataset that can assist in understanding the rock properties and can be used for understanding the rock properties based on their integral evaluation to improve reserves estimates and production efficiency, and mitigate all the associated risks. In this work, we highlight a mineralogy workflow for integral evaluation of unconventional reservoirs, involves imaging and analysis of unconventional rocks like tight sandstones, carbonates and shales, to study effects of clay, minerals and diagenetic processes and to carry out fast and accurate computations of rock properties, such as porosity and pore geometry (pore size, connectivity and distributions), absolute and relative permeability, fracture network, and flow simulations.